If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8p + 2 = 4p Reorder the terms: 2 + 8p = 4p Solving 2 + 8p = 4p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-4p' to each side of the equation. 2 + 8p + -4p = 4p + -4p Combine like terms: 8p + -4p = 4p 2 + 4p = 4p + -4p Combine like terms: 4p + -4p = 0 2 + 4p = 0 Add '-2' to each side of the equation. 2 + -2 + 4p = 0 + -2 Combine like terms: 2 + -2 = 0 0 + 4p = 0 + -2 4p = 0 + -2 Combine like terms: 0 + -2 = -2 4p = -2 Divide each side by '4'. p = -0.5 Simplifying p = -0.5
| -5(x+1.2)+10=24 | | s-10=20.37 | | 8x+14=8x-19 | | 8x+14=-4x-19 | | 6.1=-logx | | -9y+-1[2(1+3y)+6]=5y | | -3x+3=4x-18 | | 2h+7=65 | | 7(r+6)=34 | | 3[5+-3(x+-4)]=2x+9 | | 3(1+-2c)+-4=-2(3c+-1) | | 2(x+8)=2(x+11) | | 3(1-2c)-4=-2(3c-1) | | -9x+3=-x+99 | | -3x^2+13x-4= | | q=c-d | | 2-(m-30)=-6m | | 6y-2[7(1y+1)+4]=10y | | 8x+15=-4x+63 | | 12a-6+8=2 | | -3x^2+13-4= | | 15x-10=9x+26 | | 4d+d=40 | | x^2+11x+2= | | 6+-1(8-4m)=2(2m-1) | | 3x+9=6x+4 | | x^2-36x=8140 | | 8(x-.75)+12=-10 | | 1-4n=29 | | F(x)=13x+7 | | -1x-3=-2x-4 | | 5-(8+10)=8+5 |